Ergative as Perfective Oblique. (3rd September 2018) - Bjorkman, Bronwyn M.
Abstract: Many languages with ergative systems of case or agreement exhibit splits in their alignment. Viewpoint aspect is a common basis for such splits, with perfective aspect often associated with ergative alignment and imperfective with the absence of ergativity (Moravcsik1978, Silverstein1976 ). Recent work has argued that splits arise from properties of the imperfective that disrupt otherwise‐available mechanisms of ergative alignment (Laka2006, Coon2013a ). This article argues rather that the perfective can be a source of ergative case, and specifically that ergative alignment in Hindi‐Urdu arises from the intersection of two different ways of expressing perfective aspect, each attested independently in other languages: the first is the use of oblique case to mark perfect or perfective subjects, while the second is a morphosyntactic sensitivity to transitivity, a hallmark of auxiliary selection in Germanic and Romance languages. The result is a more unified view of the morphosyntax of perfective aspect, though at the cost of a nonunified account of aspectually split ergativity.